Produksi Film Pendek di Era Digital bagi Guru dan Siswa - Rahmadani, Rina (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2025)
Rapid advancement of communication technology has brought both opportunities and challenges for the short film industry in Indonesia. With the increasing accessibility of digital tools, particularly smartphones, individuals, especially youth, can produce short films at relatively low costs. Furthermore, the digital era offers a variety of platforms for showcasing these films to broad audiences, which has led to a growing interest in short film production nationwide. In response, short films are increasingly recognized by established production houses as a medium for talent discovery and creative experimentation. However, despite the ease of access to technology, developing skilled and creative young filmmakers remains a considerable challenge. Therefore, structured training programs for high school and vocational students have become essential. These initiatives are not only a form of community engagement by higher education institutions but also a strategic effort to contribute to the growth of Indonesia’s creative industry, particularly in the area of short filmmaking. The training emphasizes a comprehensive approach, combining theoretical knowledge with practical experience. Students are guided through the complete production process, from pre-production to post-production utilizing modern digital technologies to enhance their technical and creative skills, thereby preparing them to participate meaningfully in the evolving landscape of digital film production.